2015
DOI: 10.3389/fncel.2015.00105
|View full text |Cite
|
Sign up to set email alerts
|

Aged neuronal nitric oxide knockout mice show preserved olfactory learning in both social recognition and odor-conditioning tasks

Abstract: There is evidence for both neurotoxic and neuroprotective roles of nitric oxide (NO) in the brain and changes in the expression of the neuronal isoform of NO synthase (nNOS) gene occur during aging. The current studies have investigated potential support for either a neurotoxic or neuroprotective role of NO derived from nNOS in the context of aging by comparing olfactory learning and locomotor function in young compared to old nNOS knockout (nNOS−/−) and wildtype control mice. Tasks involving social recognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Pharmacological systemic inhibition of nNOS is known to have positive effects on anxiety-like behaviors [6]. In addition, a recent study has reported that lack of NO release via nNOS may protect animals to some extent against age-associated neurodegenerative changes [13]. Thus, this result suggests that NO derived from nNOS by aging acts as a neurotoxin rather than a neuroprotectant.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Pharmacological systemic inhibition of nNOS is known to have positive effects on anxiety-like behaviors [6]. In addition, a recent study has reported that lack of NO release via nNOS may protect animals to some extent against age-associated neurodegenerative changes [13]. Thus, this result suggests that NO derived from nNOS by aging acts as a neurotoxin rather than a neuroprotectant.…”
Section: Discussionmentioning
confidence: 91%
“…These findings also suggest possible regional differences in nNOS expression in the aged brain. In this regard, a previous study reported that nNOSÀ/À mice were protected from age-associated decline in olfactory learning tasks [13]. However the role of nNOS on anxiety in aged mice is not well known.…”
Section: Introductionmentioning
confidence: 96%
“…This theoretical study of nNOS SUMO-ylation provides a new pathological outlook to nNOS inhibition in cognitive decline and myopathies (Kelley et al, 2009(Kelley et al, , 2011Ito et al, 2013;Pavesi et al, 2013;Baldelli et al, 2014;James et al, 2015). Generally, the hyperactivity of nNOS produces excessive nitrogen oxide, which is toxic to neurons after acute brain injury (Yu et al, 2008;Zhou et al, 2010;Yin et al, 2013;Favié et al, 2018;Qu et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…Neuronal nitric oxide synthase (nNOS), an enzyme constitutively expressed and of high levels in the mammalian brain and skeletal muscle, catalyzes the conversion of L-arginine to nitric oxide. Previous studies have suggested that nNOS is required for learning and long-term memory (Kelley et al, 2009(Kelley et al, , 2011Pavesi et al, 2013;James et al, 2015), as well as skeletal muscle contraction (Ito et al, 2013;Baldelli et al, 2014). However, excessive activation of nNOS in the neurons results in oxidative and nitrosative stress, which is associated with neuronal loss in various neuropsychiatric disorders including hypoxic-ischemic encephalopathy (Yu et al, 2008;Yin et al, 2013;Favié et al, 2018), ischemic stroke (Zhou et al, 2010), and traumatic brain injury (Qu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As no significant differences were detected between experimental groups, it seems that the absence of nNOS directly affects olfaction in mice. Other published work ( James et al, 2015 ) describes that nNOS-KO mice show better olfactory learning and increased locomotor ability compared to wild-type animals. Apparently, these results seem to contradict ours, both for the buried food test and in the movement analyses.…”
Section: Discussionmentioning
confidence: 96%